"Sons of the West" leadership academy: Examining impact on community connectedness, leadership and self‐efficacy. (19th June 2019) - Chamravi, Daniel; Di Benedetto, Mirella; Naccarella, Lucio
Abstract: Issue addressed: Australian men experience poorer health, have reduced help‐seeking behaviours, engage in unhealthy coping mechanisms and suicide rates are disproportionately high, compared to Australian women. The "Sons of the West" (SOTW) Premiership Program is an Australian men's physical and mental health promotion program, which includes a Leadership Academy (LA), so that Premiership Program graduates can further develop skills and become leaders in improving male health. The aim of this research study was to determine if the SOTW Leadership Academy improved community connectedness, leadership attributes and self‐efficacy amongst LA graduates. Methods: Sixty‐seven Australian males ( M = 53.42, SD = 11.80, age range: 20‐72), from two groups (Premiership Program graduates who completed the LA and those who only completed the Premiership Program) completed three self‐rated questionnaires on community connectedness, self‐efficacy and leadership qualities. Results: There was a significant difference between the two groups, showing that LA graduates had increased levels of leadership skills, self‐efficacy and community connectedness compared to those who did not complete the LA. Conclusion: This study indicates that a men's health program can not only engage and improve the health of men, but also help them develop skills and enhance their own strengths, so that they can improve the health and well‐being of others. So what?: The development of leadership pathways and capacity building, embedded within health promotion programs, is an important aspect of improving health and well‐being. Summary: Australian men experience poor health. Health promotion strategies may be able to improve their health, and developing capacity of leaders within communities to help men (and women) improving their own physical and mental health is a key part of this. We think that leadership skills, self‐efficacy and community connectedness may play a role.